FACTORS AFFECTING AND PROVIDING A M (Singaporean Journal of Business Economics and Management, 2021)
Objective: The main purpose of this research is to "design and present a model for holographic information centers" which is examined by identifying the effective factors in an information center and its holographic features.Methodology: In the 21st century, holographic or holistic thinking was formed. One of the features of this period is the attention to unity and plurality. This thinking was influential in many sciences, especially the humanities. In this new pattern of thinking about each holographic phenomenon, we consider the following and choose the appropriate approach based on it. a) Unity and integrity of all components in the world; b) The total is greater than the sum of the components, and the self-organization of the components creates a general order; c) Every phenomenon contains total information and that whole is also a part of a larger whole; d) The relationship between components and the influence of phenomena on each other; e) Change in each component affects the whole, and change in the whole is possible only by changing the components; f) Every phenomenon has an esoteric order that is not separate from it but cannot be seen because it is hiddenResearch Findings: Given that information centers are a kind of organization. Therefore, an attempt has been made to extract the holographic concept in the organizational field. Then, after identifying the sources related to the principles of holography in the field of organization, by searching for these principles in scientific sources, some related sources should be extracted. The holographic pattern brought about fundamental changes in the structure and architecture of new organizations and the storage of information and the science of organizing information. Information centers as data-driven organizations need sufficient response to change and consequently organizational change in today's world to survive. In fact, the activity of a data-driven organization in competition with other organizations is full of uncertainty and complexity, which depends on the organization's ability to manage organizational change. The evolution of new information centers has a holographic nature in which component changes affect the entire system and system changes affect components. A holographic structure that has the ability to reflect holistically on any of the components can lead to deformation. The findings showed that a comprehensive environment, efficient human capital, dynamic capacity building, increased self-management, intelligent structure and dependence on holographic information centers are effective. In this research, in order to investigate the relationships, the structural equation method by PLS software has been used. After extracting the resources to use the content analysis method, the keywords in the resources are collected and ranked by Excel software. After examining the meaning of each keyword, the indicators were extracted and refined and similar items were merged, which finally, according to the key concepts of holography, its principles are extracted.